A new β-tetralonyl glucoside from the Santalum album derived endophytic fungus Colletotrichum sp. GDMU-1. Issue 3 (1st February 2019) - Liu, Weiyang; Chen, Senhua; Li, Jing; Yang, Xuemei; Yan, Chong; Liu, Hongju
Abstract: A new β -tetralonyl glucoside, methylberchemiaside (1 ), along with five known compounds (2–6 ) were isolated from a fungus Colletotrichum sp . GDMU-1 derived from the leaves of Santalum album . Their structures were determined by detailed analysis of spectroscopic data. All compounds were tested for the inhibitory effects on the nitric oxide (NO) production in lipopolysaccharide (LPS)-treated RAW264.7 cells. Among them, compounds4 and5 showed moderate anti-inflammatory activity with IC50 value of 30.4 and 8.9 μM, respectively. Abstract :